Changing of the guard leaves Cray out - Anderson, Christopher (Nature (London), 1992)
A shift from traditional supercomputers to massively parallel machines has left the industry's founder, Seymour Cray, with no products and no customers. Cray Computer's stalled efforts to launch new products are discussed.